Design and Simulation of Smart Bolt Based on Zno Piezoelectric Thin Film Sensor - Mo, Guowei; Cui, Yunxian; Yin, Junwei; Gao, Pengfei; Safaei, Babak (IOS Press BV, 2022)
In order to solve the coupling error problem of smart bolt, the coupling model of piezoelectric thin film sensor and bolt is established by using piezoelectric constitutive equation. The size parameters of ZnO piezoelectric film sensor are simulated and analyzed by finite element method using Comsol software M10×1.5 piezoelectric thin film sensor is prepared on the bolt. First, the sensors of different piezoelectric materials are compared, and then the shape, size and thickness of the piezoelectric materials of the sensor are simulated; the size and thickness of electrode material are simulated. The simulation results show that the piezoelectric material is ZnO, the shape is round, the piezoelectric material size is 10 mm, the piezoelectric thickness is 1000 nm, the electrode material size is 6 mm, and the electrode thickness is 200 nm. ZnO piezoelectric thin film sensor was fabricated with this material and size. © 2022 The author and IOS Press.
2022 International Conference on Smart Manufacturing and Material Processing, SMMP 2022 -- 2022-08-12 through 2022-08-13 -- Virtual, Online -- 184515
Keywords: Comsol simulation; Finite element method; mathematical model; piezoelectric thin film sensor; Smart bolt; ZnO piezoelectric materials